Low Vitamin D Level and Impact on Severity and Recurrence of Clostridium difficile Infections. Issue 1 (January 2015) - Abdelfatah, Mohamed; Nayfe, Rabih; Moftakhar, Bahar; Nijim, Ala; El Zoghbi, Maysaa; Donskey, Curtis J.; Kandil, Hossam; Watkins, Richard R.
<x xml:space="preserve">Abstract</x> Background Clostridium difficile infection (CDI) has recently markedly increased, incurring greater health care–associated costs and hospitalizations especially in vitamin D deficient patients. Accordingly, the aim of this study was to evaluate the relationship between low vitamin D levels and the severity and recurrence of CDI. Methods A retrospective case-control study evaluated patients hospitalized between 2007 and 2013 with CDI and a positive C. difficile toxin assay. Severe complicated CDI was defined based on (1) laboratory or radiological criteria correlated clinically and (2) sepsis requiring intensive care unit admission. Recurrent CDI (RCDI) was defined as a new episode of diarrhea occurring within 90 days of resolution of the initial episode for at least 10 days after discontinuing therapy and confirmed by positive stool C. difficile toxin assay or polymerase chain reaction. Patients were divided into 4 groups based on vitamin D level (ng/mL): severely deficient (<10), insufficient (10-19.9), predeficient (20-29.9), and control group (≥30). Results Two hundred seventy-one patients were diagnosed with CDI, of which 48 had RCDI distributed as 5 (12.5%), 15 (16.1%), 10 (15.6%), and 13 (17.5%) patients in each of the aforementioned groups, respectively (P= 0.55). Severe complicated CDI was identified in 7 (17.5%), 17 (18.2%), 9 (14%), and 3 (4%) patients, respectively (P = 0.04). Thirty-day mortality was 1 of 40, 1 of 93, 2 of 64, and 2 of 74 patients, respectively (P = 0.43). Conclusions Normal vitamin D level has a protective effect against severe CDI, and low vitamin D is associated with greater severity of CDI but not with an increased risk of RCDI or 30-day mortality.